Analysis of fluoride concentration in solutions prepared at dispensing pharmacies - Eduardo Pizzatto; Estela Maris Losso; Melina Carolina Miranda; Vivian Danielle de Souza; Felipe Belmonte Archetti (Revista Sul-Brasileira de Odontologia, 2012)
Introduction: Fluoride plays an important role in oral health promotion and is considered important in dental caries prevention both in children and adults. Fluoride is widely used at high-risk conditions of caries, when the use of fluoride-containing mouthwashes is recommended, considering that fluoride itself reduces the risk of dental caries. Objective: To evaluate the fluoride concentration in solutions prepared at different dispensing pharmacies in the city of Curitiba – PR, Brazil. Material and methods: The analysis of fluoride concentration was preformed through Ion Chromatography method (DIONEX). Results: The results obtained through this analysis showed that all solutions presented fluoride concentration above that required in the dentist’s prescription, varying between 5.48% and 24.02% more fluoride, at absolute concentration. Conclusion: This finding highlights the increasing risk of fluoride acute intoxication in cases of accidental ingestion of the solution.